Christians and missionaries in India: cross-cultural communication since 1500, with special reference to caste, conversion, and colonialism - Frykenberg, Robert Eric; Low, Alaine M. (W.B. Eerdmans Pub, 2003)
Introduction : dealing with contested definitions and controversial perspectives ; Christians in India : an historical overview of their complex origins / Robert Eric Frykenberg -- First European missionaries on Sanskrit grammar / Iwona Milewska -- Country priests, catechists, and schoolmasters as cultural, religious, and social middlemen in the context of the Tranquebar mission / Heike Liebau -- Tanjore, Tranquebar, and Halle : European science and German missionary education in the lives of two Indian intellectuals in the early nineteenth century / Indira Viswanathan Peterson --Christianity, colonialism, and Hinduism in Kerala : integration, adaptation, or confrontation? / Penelope Carson -- Constructing "Hinduism" : the impact of the Protestant missionary movement on Hindu self-understanding / Geoffrey A. Oddie -- Receding from antiquity : Hindu responses to science and Christianity on the margins of empire, 1800-1850 / Richard Fox Young -- "Pillar of a new faith" : Christianity in late-nineteenth-century Punjab from the perspective of a convert from Islam / Avril A. Powell -- Missionaries and print culture in nineteenth-century Assam : the Orundoi periodical of the American Baptist mission / Jayeeta Sharma -- The Santals, though unable to plan for tomorrow, should be converted by Santals / Marine Carrin and Harald Tambs-Lyche -- Christian missionaries and Orientalist discourse : illustrated by materials on the Santals after 1855 / Peter B. Andersen and Susanne Foss -- Glimpses of a prominent Indian Christian family of Tirunelveli and Madras, 1863-1906 : perspectives on caste, culture, and conversion / E. M. Jackson -- Social mobilization among people competing at the bottom level of society : the presence of missions in rural south India, ca. 1900-1950 / Gunnel Cederl(c)œf -- From Pentecostal healing evangelist to Kalki avatar : the remarkable life of Paulaseer Lawrie, alias Shree Lahari Krishna (1921-1989) : a contribution to the understanding of new religious movements / Michael Bergunder -- Praising baby Jesus in Iyecupiran Pillaitamil / Paula Richman
Includes bibliographical references and index
Keywords: Indien; Bibliografie; Aufsatzsammlung; Geschichte 1500-2002; Christentum; Geschichte 1500-2000; Mission